The electron-phonon interaction at deep Bi2Te3-semiconductor interfaces from Brillouin light scattering. Issue 1 (December 2017) - Wiesner, M.; Trzaskowska, A.; Mroz, B.; Charpentier, S.; Wang, S.; Song, Y.; Lombardi, F.; Lucignano, P.; Benedek, G.; Campi, D.; Bernasconi, M.; Guinea, F.; et al.
Abstract It is shown that the electron-phonon interaction at a conducting interface between a topological insulator thin film and a semiconductor substrate can be directly probed by means of high-resolution Brillouin light scattering (BLS). The observation of Kohn anomalies in the surface phonon dispersion curves of a 50 nm thick Bi2 Te3 film on GaAs, besides demonstrating important electron-phonon coupling effects in the GHz frequency domain, shows that information on deep interface electrons can be obtained by tuning the penetration depth of optically-generated surface phonons so as to selectively probe the interface region, as in a sort ofquantum sonar .